A decapolar 25‐mm‐diameter circular mapping catheter with improved detection of pulmonary vein potential disappearance in cryoballoon ablation. Issue 3 (14th May 2019) - Matsuda, Yasuhiro; Masuda, Masaharu; Asai, Mitsutoshi; Iida, Osamu; Okamoto, Shin; Ishihara, Takayuki; Nanto, Kiyonori; Kanda, Takashi; Tsujimura, Takuya; Okuno, Shota; Tsuji, Aki; Mano, Toshiaki
Abstract: Background: Disappearance of pulmonary vein (PV) potentials is an important indicator of successful PV isolation during cryoballoon ablation. Conventional octapolar 20‐mm‐diameter circular PV mapping catheters occasionally fail to identify persistent PV potentials. A new decapolar 25‐mm‐diameter circular PV mapping catheter has been introduced to improve the detection of PV potentials and their elimination. We compared the detection rates of PV potential disappearance between the decapolar and the octapolar PV mapping catheters. Methods and Results: A total of 44 consecutive patients (175 PVs) undergoing initial cryoballoon ablation for atrial fibrillation were included. The decapolar catheter was used for 79 (45%) PVs in 20 (45%) patients. There was no difference in left atrial diameter or PV diameter in patients mapped with the two catheters. The decapolar mapping catheter demonstrated a significantly higher detection rate of PV potential disappearance than the octapolar catheter. The need for touch‐up ablation was similar between the two groups (5% vs 8%, P  =   0.39). When PV potentials were identified, the decapolar catheter detected significantly higher‐amplitude PV potentials than the octapolar catheter. In multivariate analysis, use of the decapolar catheter was an independent predictor of the detection of PV potential disappearance. Conclusions: The decapolar PV mapping catheter demonstrated improved detection of PV potential disappearance in cryoballoon PV isolation.